The symptoms evolution of long COVID‑19 (SE-LC19): a new patient-reported content valid instrument - Diana Rofail; Selin Somersan-Karakaya; Eleftherios Mylonakis; Julia Y. Choi; Krystian Przydzial; Sarah Marquis; Yuming Zhao; Mohamed Hussein; Thomas D. Norton; Anna J. Podolanczuk; Gregory P. Geba (SpringerOpen, 2024)
Abstract Background The field of long COVID research is rapidly evolving, however, tools to assess and monitor symptoms and recovery of the disease are limited. The objective of the present study was to develop a new patient-reported outcomes instrument, the Symptoms Evolution of Long COVID‑19 (SE-LC19), and establish its content validity. Methods The 40-item SE-LC19 instrument was developed based on patient-relevant empirical evidence from scientific literature and clinical guidelines that reported symptoms specific to long COVID. A 2-part mixed-method approach was employed. Part 1: Qualitative interviews with a purposive sample of 41 patients with confirmed long COVID were conducted for the content validation of SE-LC19. During cognitive debriefing interviews, patients were asked to describe their understanding of the instrument's instructions, specific symptoms, response options, and recall period to ensure its relevance and comprehensiveness. Five clinicians of different medical specialties who regularly treated patients with long COVID were also interviewed to obtain their clinical expert opinions on SE-LC19. Part 2: Exploratory Rasch Measurement Theory (RMT) analysis was conducted to evaluate the psychometric properties of the SE-LC19 data collected during the interviews. Results Overall, patients reported that the instructions, questions, recall period, and response options for SE-LC19 were comprehensive and relevant. Minor conceptual gaps reported by patients captured nuances in the experience of some symptoms that could be considered in future studies. Some patients suggested a revision of the recall period from 24 h to 7 days to be able to capture more symptoms given the waxing and waning nature of some symptoms. Clinicians found the instrument comprehensive with minimal suggestions regarding its content. Exploratory RMT analyses provided evidence that the SE-LC19 questionnaire performed as intended. Conclusion The present mixed-methods study in patients with confirmed long COVID supports the content validity and applicability of the SE-LC19 instrument to evaluate the symptoms of patients with long COVID. Further research is warranted to explore the psychometric properties of the instrument and refine a meaningful and robust patient-relevant endpoint for use in different settings such as clinical trials and clinical practice to track the onset, severity, and recovery of long COVID.